Whirl Sign and Midgut Volvulus: An Unusual Cause of an Acute Abdomen in an Adult Patient - Eoghan P. Burke; Munir Saeed; Maham Mahmood; Cathal Hayes; Mohamed Salama; Ibrahim Ahmed (Case Reports in Surgery)
We report the case of a 50-year-old lady who presented to the emergency department complaining of a two-day history of colicky right upper quadrant (RUQ) pain, which radiated through to her back, associated with nausea, anorexia, and two episodes of vomiting that day. She was found to be tender in the RUQ. Her blood tests were notable for an elevated white cell count. Initial impression was of acute cholecystitis. Ultrasound of her abdomen did not identify any features of acute cholecystitis; however, a large volume of free fluid was identified within the abdomen. CT of the abdomen/pelvis was obtained which identified dilated loops of small bowel, interloop ascites, and a whirl sign highly suggestive of midgut volvulus. During laparoscopy, the midgut volvulus was found to have resolved. No cause for the volvulus could be identified, and the patient was discharged home well on postoperative day two.